PENDEKATAN PEMBELAJARAN MULTISENSORI MENGGUNAKAN KARTU HURUF SAMBIL MEMBUNYIKAN METODE FONIK UNTUK ANAK BERKEBUTUHAN KHUSUS DISLEKSIA - Nofi Kristianto; Liftiah; Ali Formen (STKIP Subang, 2026)
Dyslexia is a specific neurobiological learning disorder that affects children's phonological processing abilities, causing difficulties in reading, spelling, and understanding text despite having normal intelligence. This literature review aims to analyze the effectiveness of a multisensory learning approach using letter cards while sounding out phonics for children with special needs with dyslexia. The literature review was conducted on 28 scientific articles (15 international studies and 13 national studies) published between 2020 and 2026 from various reputable databases. The synthesis results indicate that a multisensory approach based on Orton-Gillingham and Structured Literacy that integrates letter cards (visual-tactile) with sounding out techniques (auditory-kinesthetic) is effective in improving phonemic awareness, decoding skills, reading fluency, as well as motivation and self-confidence in children with dyslexia. The reported effectiveness ranges from moderate (0.22–0.72). This approach is highly relevant in Indonesia because it is simple, inexpensive, and easily adapted to the Independent Curriculum and inclusive school conditions. However, most studies in Indonesia are still action research with small sample sizes, so more rigorous experimental research is needed in the future.